Utilização de rejeito líquido da indústria de alimentos para a produção de protease por amostras de Aspergillus spp. Isoladas da caatinga de Pernambuco. - Marinho, Jaqueline dos Santos (2021)
Currently, the huge generation of waste by the agrifood industry represents a significant environmental challenge. However, most of these residues are rich in nutrients and can serve as raw materials for the production of value-added products or as sources of renewable energy. In this context, the present work reused whey from cheese manufacturing for the production of protease by filamentous fungi isolates of the genus Aspergillus. A total of six isolates were cultivated in standard media (1% gelatin and 25% whey alternative) for a period of 96 hours, at 150 rpm and 28 ºC to select the best protease producer. Subsequently, a 2³ factorial design was carried out to investigate the influence of the independent variables temperature, pH and whey concentration on the production of protease in submerged fermentation by the selected strain. According to the results Aspergillus sp. UCP 1290 was selected for its high proteolytic activity of 28.75 and 37.33 (U/mL) in standard and alternative media, respectively. By carrying out the factorial planning of the factorial planning with the selected isolate, it was possible to identify maximum proteolytic activity (129.80 U/mL) with Aspergillus sp. UCP 1290 in planning condition 4 (temperature of 32 ºC; pH 8.0 and serum concentration of 20%.) The analysis of variance showed that all independent variables tested were significant for the production of the protease. The whey concentration was the most significant independent variable, but it negatively influenced the enzyme production, indicating that lower whey concentrations can favor a higher enzyme production. On the other hand, the temperature was the one that most influenced the production of the protease. The enzyme produced showed high catalytic activity at pH 7.0 and at 60 ºC, which suggests that it is a neutral protease active at high temperature. Thus, whey can be used as the only substrate for Aspergillus sp. UCP 1290 for the production of neutral proteases active at temperatures used in industrial bioprocesses.